African spiritual phenomena and the probable influence on African families - Knoetze, Johannes J. (In die Skriflig, 2019)
African spirituality is a holistic concept that stemmed from the historical, cultural and religious heritage of Africa, and includes among others, folktales, beliefs, rituals and culture. African spiritualities must be understood as originated from Africa's soil, but also developed through contact with people from other countries and continents. The African independent or indigenous churches play an important role in the establishing of African Christian spiritualities. This article distinguishes and gives attention to the influence of African traditional spiritual phenomena as well as a 'globalised Africa spiritual' phenomenon on African families. When the influence on African families are discussed, it is done from a Christian point of view, and for this reason the article concludes with the role of the missional church and parents in the spiritual formation of their children.
free
Keywords: AFRICA; African traditional religion; CHRISTIAN spirituality; CLERGY; CULTURAL property; FAMILIES; SPIRITUAL formation; SPIRITUALITY; families; globalisation; missional church; spirituality